Effect of organic extracts of Cafure leaves (Eucalyptus camaldulensis Dehn.) on mosquitoes (Anopheles arabiensis Patton.) - Elsiddig, Fathelrahman (Gezira Journal of Agricultural Science; Vol 9 No 2 (2011), 2011)
Laboratory experiments were conducted at the National Malaria Centre, Sinnar State, Sudan to investigate the effects of organic extracts of Cafure leaves ( Eucalyptus camaledulensis Dehn.) against malaria vector in Sudan ( Anopheles arabiensis ) Patton (Diptera:Culicidae). The larvicidal activities of different concentrations of ethanol and hexane extracts were measured according to the WHO standards for testing susceptibility of mosquito larvae to insecticides. The effects of extracts on repellency, oviposition deterrency and mortality of adult insects were also measured. Results indicated that hexane extract showed the best larvicidal effect with LC 50 of 127.9 mg ℓ -1 . It proved superiority over the standard larvicide Temphos ® in the initial levels, meanwhile, ethanol extract exerted poor larvicidal effect (LC 50 8276 mg ℓ 1 ). Results showed that hexane extract at 10% concentration repelled mosquitoes, for two and a half hours. However, ethanol concentrations depicted no repellency. All the tested extracts exhibited oviposition deterrency properties but had little insecticidal activities.      تم اجراء تجارب معملية فى المركز القومى للملاريا بولاية سنار لمعرفة تاثير مستخلصات عضوية من اوراق  الكافور على البعوض الناقل للملاريا بالسودان ( Anopheles arabiensis Patton.). تم قياس النشاط القاتل لليرقات وذلك لتركيزات مختلفة من مستخلصات الايثانول والهكسان تبعاً لمقاييس منظمة الصحة العالمية المستخدمة لاختبار حساسية يرقات البعوض للمبيدات. تم اختبار المستخلصات ضد الحشرة الكاملة للانوفليس وذلك بحساب التاثير الطارد كل نصف ساعة، والتاثير المانع لوضع البيض والقاتل للحشرة الكاملة بعد 24 ساعة من التعرض. اوضحت النتائج ان مستخلص اوراق الكافور الهكسانى اعطى اعلى تاثير قاتل لليرقات وذلك يتركيز نصفى قاتل 127,9 مجم/لتر-1، مع تفوق على المبيد القياسى تمفوس فى المستويات الاولى للتركيزات. اظهرت النتائج ايضاً ان المستخلص الهكسانى بتركيز 10% هو المعاملة الوحيدة التى ادت لطرد الحشرة الكاملة وذلك لفترة زمنية امتدت  لساعتين. اظهرت المستخلصات تحت الاختبار خصائص مانعة لوضع البيض مع قليل من المميزات القاتلة للحشرة الكاملة.